Civil society and children rights in Zimbabwe: case of justice for children organization in Budiriro district in Harare 2013 to present. - Midzi, Nyasha Adrian (Midlands State University, 2017)
Abuse of children has been at peak in Zimbabwe henceforth the need for NGOs such as Justice for Children to step in as agents that promotes the rights of children. The research is entitled civil society and children rights in Zimbabwe: Case of Justice for Children Organisation in Budiriro District Harare 2013 up to present. This research then seeks to determine the activities and contributions of Justice for Children in fighting against the violations of children rights. An analysis of the causal factors to the violations of children rights was also the major thrust of the research and it was noted that ignorance of the children’s law, separation of parents, death of parents and harmful cultural and social practices were the leading causal factors of violating the rights of children. Two leading theories that were the Choice theory and the Interest theory were the major anchors of the study as they fully address children issues. Qualitative and quantitative approach was then used as the research methodology in which the combination of the two methods complemented each other and allowed for complete analysis. Main actors which are dominant in the field of promoting the rights of children and the challenges they encounter were also the major concerns of the research and also the success these organisation have achieved up to the present day. Recommendations were forwarded in which the constitution was the major point of concern that it should be reformed so as to suite the best interests of children and the conclusion of the whole matter was that the violation of children rights in Zimbabwe is mainly caused by social harmful and cultural practices.